Pendampingan Analisis Data dan Penulisan Laporan Hasil Penelitian bagi Guru Sekolah di Kabupaten Seram Bagian Timur: Penguatan Literasi Riset melalui Program FKIP Mengajar - Rumahlewang, Emma; Matitaputty, Johanna; Latar, Idris Mohamad; Dulhasyim, Ashari Bayu (Universitas Pattimura, 2025)
This mentoring program was motivated by the limited ability of teachers in East Seram Regency to analyze data and prepare community service reports that meet academic standards. The program aimed to enhance teachers’ competence through practice-based training in data analysis and scientific report writing. The implementation used a participatory approach combining workshops, coaching clinics, and peer mentoring involving lecturers, students, and teachers from various educational levels. Results showed significant improvement in teachers’ analytical skills, report structuring, and motivation to publish academic works. The activity also established a professional network of teacher-writers committed to continuing academic collaboration. This program demonstrates the effectiveness of contextual, reflective mentoring models for empowering teachers in island regions. Recommendations emphasize institutional support and program continuity in remote areas.